The Role of Gasdermin D and CRP as Risk Markers of Postoperative Delirium in Patients Undergoing Spine Surgery: A Prospective Cohort Study - Bagade, Ashwini; Lakra, Anshu Priyanka; Mohan, Akshita; Trivedi, Saurabh; Thawre, Pooja; Ghangjoria, Vaishali (Journal of Neonatal Surgery, 2025)
Aim: To evaluate the role of Gasdermin D and C-reactive protein (CRP) as biomarkers for predicting the risk of postoperative delirium (POD) in elderly patients undergoing spine surgery. Material and Methods: This prospective cohort pilot study was conducted over one year at the Department of Anaesthesiology, R D Gardi Medical College Ujjain. Thirty-five patients aged ≥60 years, classified as ASA I or II and scheduled for elective spine surgery under general anaesthesia, were included. Patients with pre-existing cognitive impairment, systemic infections, or malignancies were excluded. Preoperative and 48-hour postoperative CRP and Gasdermin D levels were measured using ELISA. Delirium assessment was performed daily for seven days post-surgery using CAM or CAM-ICU. Statistical analyses included logistic regression and ROC curve analysis, with p < 0.05 considered significant. Results: Out of 35 patients, 9 (25.71%) developed POD. Patients with delirium showed significantly lower MMSE scores and higher preoperative CRP (9.2 ± 1.8 mg/L) and Gasdermin D levels (55.6 ± 8.9 pg/mL) than those without delirium (CRP: 5.6 ± 1.4 mg/L; Gasdermin D: 37.8 ± 6.3 pg/mL). Postoperative levels further increased in the POD group (CRP: 16.8 ± 2.6 mg/L; Gasdermin D: 74.2 ± 9.4 pg/mL). ROC analysis showed high predictive accuracy with AUCs of 0.86 for postoperative CRP and 0.91 for postoperative Gasdermin D. Sensitivity and specificity were highest for postoperative Gasdermin D at a cut-off of >65 pg/mL (100% and 84.6%, respectively). Conclusion: Elevated CRP and Gasdermin D levels, both pre-and postoperatively, were significantly associated with the development of POD. Gasdermin D exhibited superior predictive performance, suggesting its utility as a novel biomarker. Prolonged surgical duration and higher blood loss were additional risk factors. These findings support the integration of inflammatory biomarkers into perioperative risk assessment protocols.